2021
DOI: 10.2147/idr.s342964
|View full text |Cite
|
Sign up to set email alerts
|

Explorative Analysis of Treatment Outcomes of Levofloxacin- and Moxifloxacin-Based Regimens and Outcome Predictors in Ethiopian MDR-TB Patients: A Prospective Observational Cohort Study

Abstract: Purpose/Background: Although Ethiopia is among the thirty high multi-drug resistant tuberculosis (MDR-TB) burden countries in the world, comparative therapeutic efficacy of moxifloxacin and levofloxacin has not been explored, particularly in MDR-TB patients. We therefore aimed to prospectively compare clinical outcomes and determine potential predictors of the outcomes among patients on moxifloxacin or levofloxacin-based MDR-TB drug regimens. Methods: We analyzed clinical parameters and laboratory data of eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The treatment success rate was 62.1%, similar to the results in other countries [ 32 , 33 ]. Although several studies have concluded that treatment delays were associated with poor treatment outcomes [ 8 , 9 ], our research reached a different conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…The treatment success rate was 62.1%, similar to the results in other countries [ 32 , 33 ]. Although several studies have concluded that treatment delays were associated with poor treatment outcomes [ 8 , 9 ], our research reached a different conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…This is a follow-up of our previous prospective cohort study, 23 enrolling MDR-TB/RR-TB patients in four hospitals of Southern Ethiopia, namely, Butajira, Yirgalem, Arbaminch, and Nigist Eleni Mohammed Memorial teaching hospitals. These hospitals were among the first four hospitals identified by the Ministry of Health of Ethiopia as treatment initiative centers for MDR-TB treatment in Southern Ethiopia.…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Patients in the experimental group were given the chemotherapy regimen combined with levofloxacin: 2HRZEL/6HRE, isoniazid 0.3g daily at a draught; rifampicin 0.45g daily at a draught; pyrazinamide 0.5g daily, tid; ethambutol 0.75 g daily at a draught; levofloxacin 0.8g daily, orally. 10 All patients underwent sputum culture + drug sensitivity test before treatment. After two months of treatment, patients were switched to the HRE regimen for six months, with the drug application method and dose as above.…”
Section: Methodsmentioning
confidence: 99%